My papa rich - Ryon, Lee; Aaron, Koh; Wang, Lei; Jack, Neo; Teddy, Chin; Mindee, Ong; Rosa, Chong (Kuala Lumpur : Film Kingdom Group Sdn. Bhd., 2014)
Yang is a widower who is used to living a solitary life. He lives a simple and poor life. His eldest daughter is married and resides in Kuala Lumpur, his second daughter is still studying in Singapore and his youngest son works as a small-time salesman. Yang real troubles begins when he realizes that he cannot afford to celebrate the coming Chinese New Year. However, a chance encounter with his long-time friend, Lin who has become a millionaire, changes Yang's life as Lin offers Yang a once in a life time chance of becoming a millionaire for a month.
Special features: The making of.
Director of photography, Stephen Chua ; music director, Tan Yen Hue ; editor, Shiao Yun Ku.
Wang Lei, Jack Neo, Teddy Chin, Mindee Ong, Rosa Chong.
LPF: U
DVD format, Stereo (Mandarin), Dolby Digital.
In Mandarin with optional English, Malay and Chinese subtitles.
Keywords: Families in motion pictures; Comedy films